Attempting to Increase the Learning Motivation of Grade X Students in Writing Expository Text Through Small Group Discussion Method Using Color Picture Media - Muhammad Nasir; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2024)
This research aims to increase the learning motivation of Class The population of this research was all class X SMA N 1 Padang Tualang, totaling 286 students, the sample for this research was 94 students. The instrument used in this research was an official letter text writing test. This research is classroom action research. The results of the research show that it can be seen that the highest score achieved by students in the ability to write expository texts before using colored picture learning media (pre-test) was 79 and the lowest score was 50 in the very poor category, while the highest score achieved by students was in the ability to write expository texts after using the media. color picture learning is 98 and the lowest score is 88 in the very good category.